What Can Be Given? What Can Be Found? A Therapist and Supervisor Consider What It Is to Hold and Let Go. (2nd January 2016) - Kandall, Elizabeth
ABSTRACT: This paper is a companion to Simone Hidary's paper. It gives a supervisor's perspective on the process of a student therapist's development. The therapist was particularly interested in defining for herself the meaning of a holding environment.